Study of Properties of Modifications Asphalt by Using Waste Oil as Replacement - Rahiman, Nik (Progress in Engineering Application and Technology, 2023)
Crude oil is one of the most mismanaged resources on the world. Inappropriate used oil handling can lead to environmental problems. However, waste oil may be recycled in a variety of methods and used in technical applications, such as a rejuvenator for asphalt binder. The objective for this study is to study the chemical properties of waste engine oil from heavy vehicle and light vehicle. In addition, the mechanical characteristics of modified asphalt are evaluated, and the performance of standard asphalt and modified asphalt with waste oil is compared. Fourier Transform Infrared Spectroscopy (FTIR) Test, Softening Point, Penetration Test and Ductility Penetration testing reveals the stiffness of changed asphalt, and stiffness of sample car waste engine oil reveals a large increase in comparison to sample motorcycle waste engine oil. Data for the motorcycle waste oil sample, contrasted, reveal that the higher the value of the waste oil mixture, the more flexible the properties of the modified asphalt. In compared to traditional asphalt, modified asphalt with vehicle waste oil was able to change the properties of asphalt because the waste engine contains chemical compounds that influence the changed.